Pendampingan Pengembangan Usaha Produksi Telur Asin “Pak Mul” Desa Sendang Melalui Pembuatan Logo, Stempel, dan Label - Tri Martuti, Nana Kariada; Khoiriyah, Laelatul; Elsa Zahara, Nurwilis (Jurnal Bina Desa, 2024)
This community service activity aims to improve the branding and marketing of Pak Mul Salted Eggs MSME products located in Sendang Village, Karanggede District, Boyolali Regency. Through the Real Work Lecture (KKN), Semarang State University students provide assistance in creating logos, stamps, and product packaging labels. The methods used include observation, determining MSMEs, creating branding, and documentation and are carried out through direct practice, where students collaborate with business owners to design an attractive visual identity. However, many MSME actors still face various challenges, including a lack of awareness of the importance of valid certification and administration, as well as the need for effective branding. Through the Real Work Lecture (KKN) program, Semarang State University (UNNES) students provide assistance to Pak Mul Salted Eggs MSMEs in Sendang Village, Boyolali, with the aim of improving branding and product packaging quality through creating logos, stamps, and labels. This program is expected to increase the competitiveness and marketing of these MSME products, which in turn helps them grow and develop in a wider market.